Cuatro medio verdales: la relacion bosques y agua en Centroamericana - Kaimowitz, D. (2001)
This paper looks at four "half-truths" about the relations between forests and water in Central America. The first is that deforestation has reduced rainfall in certain regions of Central America. The second is that forest help to maintain dry season stream flow. The third is that deforestation has led to more intense flooding. The fourth is that the region's hydroelectric reservoirs and the Panama Canal are rapidly becoming sedimented. As the name implies, the article argues that each of these has some elements of truth but other aspects that are myths. The author emphasizes that even though some of these claims are myths action still needs to be taken to avoid inappropriate deforestation and forest degradation.